2013
DOI: 10.1111/php.12147
|View full text |Cite
|
Sign up to set email alerts
|

Photooxidation Mechanism of Levomepromazine in Different Solvents

Abstract: Unwanted photoinduced responses are well-known adverse effects of most promazine drugs, including levomepromazine (LPZ, Levoprome ® or Nozinan ® ). This drug is indicated in psychiatry primarily for the treatment of schizophrenia and other schizoaffective disorders. Levomepromazine's particular sedative properties make it especially fit for use in psychiatric intensive care. Nevertheless, it is photolabile under UV-A and UV-B light in aerobic conditions resulting in the formation of its sulfoxide. The LPZ phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…The drug molecule in triplet excited state or cation radicals may interact with molecular oxygen that results in singlet oxygen generation ( Figure 6 ). Moreover, reaction with oxygen leads to the production of oxidized products [ 160 , 161 ]. It has been reported that 2-chloroderivatives undergo dechlorination and then photoreduction or substitution.…”
Section: Characteristics Of Drugs With Photosensitive Potentialmentioning
confidence: 99%
“…The drug molecule in triplet excited state or cation radicals may interact with molecular oxygen that results in singlet oxygen generation ( Figure 6 ). Moreover, reaction with oxygen leads to the production of oxidized products [ 160 , 161 ]. It has been reported that 2-chloroderivatives undergo dechlorination and then photoreduction or substitution.…”
Section: Characteristics Of Drugs With Photosensitive Potentialmentioning
confidence: 99%
“…TX and its derivatives are of particular interest due to their interesting photochemical and photophysical properties . The triplet state of TXs are mainly responsible for their photochemical and photophysical reactions.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently carried out a detailed vibrational study on the triplet state structure of the TX in the lowest excited triplet state . Even though attempts have been made to understand the triplet state photochemistry of CTX, till date, no systematic study has been reported concerning the structural aspects in both ground and lowest triplet excited states.…”
Section: Introductionmentioning
confidence: 99%